Secure and Proficient Cross Layer (SPCL) QoS Framework for Mobile Ad-hoc - santosh sahu; Sanjeev Sharma (International Journal of Electrical and Computer Engineering (IJECE), 2019)
A cross layer QoS framework is a complete system that provides required QoS services to each node present in the network. All components within it cooperate together for providing the required services. In existing QoS frameworks there is no security mechanism provided while Security is a critical aspect for QoS in the MANET environment. Cross layer QoS framework  tend to be vulnerable to a number of threats and attacks like, over/under-reporting of available bandwidth, over-reservation, state table starvation, QoS degradation,  information disclosure, theft of services timing attack, flooding attack, replay attack, and denial of service (DoS) attack,  attacks on information in transit and attacks against routing. So it is necessary when designing protocols for QoS framework, the harmony between security and QoS must be present as one impacts the others. In this work we proposed secure and proficient cross layer (SPCL) QoS frameworks which prevents from various types of threats and attacks.  The proposed SPCL QoS framework achieves better performance compared to existing QoS frameworks  in metrics of throughput, packet drop ratio, end-to-end delay, and average jitter in both condition when malicious node present in the network and when malicious node not present in the network